A survey of statistical methods for inequalities in access to healthcare—Kermanshah in West Iran - Reshadat, Sohyla; Zangeneh, Alireza; Ziapour, Arash; Farahmandmoghadam, Naser; Khosravi Shadmani, Fatemeh; Teimouri, Raziyeh; Golanbari, Shirin Zardui; Rostami, Samira (Frontiers in Applied Mathematics and Statistics, 2022)
Background: Access to medical care is one of the major issues affecting human health. This study aims to investigate inequality in access to medical care in the townships in Kermanshah, Iran. Methods: Methodology approach includes a descriptive-analytic study followed by determining the degree of development of the townships calculated in terms of access to medical care through the hierarchical cluster analysis and the combined model of human development index. Additionally, the mean center and standard distance tests are handled in a geographic information system software to identify the deployment pattern of the status of access to medical care indexes. Results: As for the ratio of physicians, nursing staff, paramedical staff, administrative staff of health care, dentists, pharmacists, hospitals, general and specialized clinics, radiology, rehabilitation centers and laboratories to a population of 10,000, the results of analyzing the findings were indicative of unequal distribution of facilities at the level of townships. This is based on The results of comparing the mean centers of population and health facilities showed that the centers of both data categories were located in Kermanshah. The two standard distances (i.e., population and health facilities) demonstrated that the health facilities witnessed more dispersion in the northwestern regions than the concentration of population in the central and southeastern regions of the province. Conclusions: The results indicated that the indexes of development of facilities and healthcare resources were not distributed equitably and with a balance between the townships of the Kermanshah Province.